الموازنات على أساس الأنشطة ومعوقات تطبيقها في المنشآت الصناعية السورية - أمين ماهر; عابدين أسامة ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعدّ الموازنات إحدى أساليب المحاسبة الإدارية التي تستخدمها المنشآت الاقتصادية من أجل تخطيط ورقابة أعمالها، وقد كانت أغلب المنشآت تستخدم نظام موازنة البنود إلا أن التطور الاقتصادي والتكنولوجي وما رافقه من تغير في توجهات الإدارة العليا للمنشآت أدى إلى قصور هذا الأسلوب عن أداء مهامه بالشكل الأمثل وظهور حاجة إلى استخدام أساليب أكثر تطورا تلبي حاجة المنشأة. وقد اقترح الباحث استخدام مدخل الموازنة على أساس النشاط والتي تعرف بأنها عملية تخطيط وتحكم في الأنشطة المتوقعة من المنظمة لاشتقاق موازنة فعالة التكاليف تعنى بحمل العمل المتنبأ به وتحقق الأهداف الإستراتيجية المتفق عليها. قام الباحث بنشر 60 استبياناً لدراسة مدى إمكانية تطبيق هذا النظام في المنشآت الصناعية السورية وتوصل إلى أن تطبيق هذا النظام يواجه بعض الصعوبات التي تعوق تطبيقه. ويقترح الباحث تدريس هذا النظام في المواد الدراسية الجامعية، وإقامة دورات مهنية للتدريب على تطبيقه، والاستعانة بخبراء خارجيين للمساعدة في تطبيق هذا النظام. Budgets are one of the Management Accounting Techniques that Economic Firms use for planning and controlling purposes. Most firms used Items budget, but the technological and economic developments and the change in the orientation of Top management in these firms made traditional budgeting out of date and unsuitable in this new environment, which in turn requires more developed techniques to satisfy the needs of the firms. The researcher proposes the use of the entrance of the Activity Based Budgeting which is a process of planning and controlling the activities expected from the organization to derive a cost-efficient budget to carry out the predicted work and achieve the strategic objectives agreed upon. The researcher has published 60 questionnaires to study the possibility of applying this system in the Syrian industrial companies and has concluded that the application of this system is facing some impeding difficulties. The researcher proposes teaching this system in university courses, and establishing vocational courses, and the use of outside experts to assist the application of this system.